1986
DOI: 10.1039/c39860000233
|View full text |Cite
|
Sign up to set email alerts
|

A new hexacarboxylate uranophile derived from calix[6]arene

Abstract: A new hexacarboxylate uranophile has been synthesised from calix [6]arene: log K (stability constant for the complex with U022+) was estimated to be 18.7.The selective extraction of uranium from sea water has attracted extensive attention from chemists because of its importance in relation to energy problems. In order to design a ligand that can selectively extract the uranyl ion (U022+), one has to overcome a difficult problem: the ligand must strictly discriminate between U022+ and other metal ions present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 2 publications
1
10
0
1
Order By: Relevance
“…2-5 It was shown that these macrocycles formed extremely stable uranyl complex, and the stability is attributed to the quasi-planar arrangement of the 5 or 6 binding groups on the lower calixarene rim. 4 This arrangement coincides with the preferred hexa-coordinate planar geometry occurring perpendicular to the U-O bonds of the linear uranyl ion. The calix[n]arene used in this work was 4-sulfonic calix [6]arene which have six hydroxyl groups on the lower rim and six sulfonate groups on the upper rim.…”
Section: Introduction Experimentalsupporting
confidence: 65%
“…2-5 It was shown that these macrocycles formed extremely stable uranyl complex, and the stability is attributed to the quasi-planar arrangement of the 5 or 6 binding groups on the lower calixarene rim. 4 This arrangement coincides with the preferred hexa-coordinate planar geometry occurring perpendicular to the U-O bonds of the linear uranyl ion. The calix[n]arene used in this work was 4-sulfonic calix [6]arene which have six hydroxyl groups on the lower rim and six sulfonate groups on the upper rim.…”
Section: Introduction Experimentalsupporting
confidence: 65%
“…[6]arene and immobilization onto APS;C [6]APS p-tert-Butylcalix [6]arene is used as the basis for derivatization which is described in Sheme 1. The syntheses of compounds 1-3 were obtained according to the previously published procedures [33], while the reaction producing C [6]APS (see Scheme 1) was described by Tabakci [27]. The hexaacid derivative of p-tert-butylcalix [6]arene 3 was obtained by hydrolysis of ester moieties of p-tert-butylcalix [6]arene (2).…”
Section: Chemical Reagentsmentioning
confidence: 99%
“…Des études cristallographiques par diffraction des rayons X (Araki et al, 1993) ont établi que les complexes de l'ion uranyle adoptent une structure pseudoplanaire hexacoordonnée, ce qui n'est pas le cas des autres cations métal-liques. Ceci suggère l'utilisation d'un macrocycle hôte ayant un arrangement coplanaire de six groupes ligands spécifiques pour l'ion uranyle (Shinkai et al, 1986(Shinkai et al, ,1987. Toutefois, des travaux concernant le calix [o]arène substitué par six fonctions acide carboxylique ont montré une diminution de la sélectivité lorsque UO$+ se trouve en compétition avec d'autres cations métalliques lors de l'extraction (Nagaski et Shinkai, 1991).…”
Section: Various Wrocyclic Mobcuiesunclassified